2014
DOI: 10.15550/asj.2014.08.235
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Analysis of the Aqueous-Alcoholic Mixtures, Prepared in Demineralized by Reverse Osmosis Water

Abstract: Abstract:The aim of the publication is to study the mechanisms of transformation of ethanol protons (ethyl rectified spirit -ERS) and water (demineralized by reverse osmosis) in the process of creating aqueousalcoholic mixtures (AAM). The methods used in the work: 1 H nuclear magnetic resonance (NMR) spectroscopy of AAM; methods of evaluation of physicochemical and organoleptic characteristics of water, ethanol, AAM. In this paper, we have established fundamentally new features in the process of creating AAM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…38 Kuzmin et al reported the thermodynamic equilibrium of ethanol and water in spirits by means of 1 H NMR spectroscopy. 39,40 Some components affecting the water-ethanol structure in spirits were reported. 41 The solvation of metal ions was reported with aged Shochu in earthenware vessel.…”
Section: Hydrogen-bonding Structure Of Water-ethanol In Spiritsmentioning
confidence: 99%
“…38 Kuzmin et al reported the thermodynamic equilibrium of ethanol and water in spirits by means of 1 H NMR spectroscopy. 39,40 Some components affecting the water-ethanol structure in spirits were reported. 41 The solvation of metal ions was reported with aged Shochu in earthenware vessel.…”
Section: Hydrogen-bonding Structure Of Water-ethanol In Spiritsmentioning
confidence: 99%
“…The most important stages in the production of vodka (Oliinyk et al, 2016(Oliinyk et al, , 2014Kuzmin et al, , 2015 [1][2][3][4][5][6][7] are the creation of water-alcohol mixtures (Kuzmin et al, 2013 [8][9][10][11][12][13][14] and processing them with activated carbon (Oliinyk et al, 2014;Mukhin et al, 2003Mukhin et al, , 2004 [2,15,16]. The quality of the activated carbon depends on the quality of the finished product (Mukhin et al, 2003(Mukhin et al, , 2004Petrov et al, 2004Petrov et al, , 2005 [15][16][17][18].…”
Section: Analysis Of Recent Researchs and Publicationsmentioning
confidence: 99%
“…The preliminary conducted 1 H NMR studies, which are described in a work (Kuzmin O. et al, 2013 [21][22][23][24], relate to the study of hydroxyl protons of AAM modifications in the process of making vodkas. The obtained results give grounds to assert a fundamental difference in the behavior AAM prepared from the alcohol and water passing through various processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the work (Kuzmin O. et al, 2013 [21][22][23][24] was established experimental evidence of stationary nature / (non-stationary) of thermodynamic balance, taking into account the organoleptic characteristics of AAM in dependence on water treatment method and time of system's functioning. However, the questions related to internal mechanism's specification and the rate of establishment of thermodynamic balance depending on type of water used in the process of creating the AAM are remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation